Technology of Obtaining Two-Layer Knitted Fabrics in a New Structure of a Flat TwoNeedle Knitting Machine with the Needles Placed in a Rubber Arrangement - J.Z.Borotov; Q.М.Хоliqov; N.М.Мusayev; М.М.Мuqimov; N.N.Yoqubjanov (Global Scientific Publishing, 2023)
Using the technological capabilities of modern double bed flat knitting machines, the technology for producing double-layer knitted fabrics of a new structure, made by arranging the needles in rib positions, has been studied.
Keywords: ribana; needle; double-layer; knitting